Legitimacy, power, and inequalities in the multistakeholder internet governance: analyzing IANA transition - Palladino, Nicola; coautor Santaniello, Mauro (Cham, Switzerland: Palgrave Macmillan, 2021)
Chapter 1. Introduction - The IANA Transition and Internet Multistakeholder Governance -- Chapter 2. Foundations, pitfalls, and assessment of multistakeholder governance -- Chapter 3. IANA functions, ICANN and the DNS war -- Chapter 4. The Institutional Design of the IANA Transition process -- Chapter 5. The Input Legitimacy of the IANA Transition Process -- Chapter 6. The Throughput Legitimacy of the IANA Transition process -- Chapter 7. The Output Legitimacy of the IANA Transition process -- Chapter 8. Conclusion: The misleading rhetoric of multistakeholderism.